Optimizing lift and rotation in diving - Golden, D.
To perform the most difficult dives requires that divers generate a greater resultant force during the takeoff from which they can achieve optimum lift and rotation. Practice sessions should focus on those movements that optimize lift and rotation. A checklist of biomechanical concepts for evaluating the takeoff should include: Full utilization of the springboard Optimizing the fulcrum setting Increasing hurdle height Moving in time with the springboard Proper body alignment during the takeoff Directing the COG as vertical as possible for maximum air time Maximizing movements that create downward forces Increasing the segmental angular velocities but starting the movement sequence later Applying segmental forces sequentially Increasing the horizontal force distance from the COG for greater rotation Assuming the somersault position earlier by minimizing the arm circle/grab pattern